Outcome of the pesticides peer review meeting on general recurring issues in physical and chemical properties and analytical methods. Issue 4 (23rd April 2019) - ,; Abdourahime, Himdata; Bura, Laszlo; Lentdecker, Chloe De; Kardassi, Dimitra; Lythgo, Christopher; Molnar, Tunde; Serafimova, Rositsa; Sturma, Juergen; Tiramani, Manuela; Vagenende, Benedicte
Abstract : This technical report reflects the outcome of the physical‐chemical properties experts' meeting on general recurring issues noted during the EFSA peer reviews of pesticide active substances under Regulation (EC) No 1107/2009. General and specific issues were identified and discussed related to the quality and level of details of the assessment reports and the adherence to the data requirements, in particular regarding analytical methods and issues related to the assessment of the impurity profiles and the proposed specifications. Conclusions and further recommendations on these issues are reported.